Effect of microstructure and temperature on the erosion rates and mechanisms of modified EB PVD TBCs - Wellman, R. G.; Nicholls, John R.; Murphy, K. S. (Elsevier Science B.V., Amsterdam., 2009)
Thermal barrier coatings (TBCs) have now been used in gas turbine engines for a number of decades and are now considered to be an accepted technology. As there is a constant drive to increase the turbine entry temperature, in order to increase engine efficiency, the coatings operate in increasingly hostile environments. Thus there is a constant drive to both increase the temperature capabilities of TBCs while at the same time reducing their thermal conductivities. The thermal conductivity of standard 7 wt% yttria stabilized zirconia (7YSZ) electron beam (EB) physical vapour deposited (PVD) TBCs can be reduced in two ways: the first by modification of the microstructure of the TBC and the second by addition of ternary oxides. By modifying the microstructure of the TBC such that there are more fine pores, more photon scattering centres are introduced into the coatings, which reduce the heat transfer by radiation. While ternary oxides will introduce lattice defects into the coating, which increases the phonon scattering, thus reducing the thermal conductivity via lattice vibrations. Unfortunately, both of these methods can have a negative effect on the erosion resistance of EB PVD TBCs. This paper compares the relative erosion rates of ten different EB PVD TBCs tested at 90Ã Â° impact at room temperature and at high temperature and discusses the results in term of microstructural and temperature effects. It was found that by modifying the coating deposition, such that a low density coating with a highly Ã¢Â Â featheredÃ¢Â Â microstructure formed, generally resulted in an increase in the erosion rate at room temperature. When there was a significant change between the room temperature and the high temperature erosion mechanism it was accompanied by a significant decrease in the erosion rate, while additions of dopents was found to significantly increase the erosion rate at room and high temperature. However, all the modified coatings still had a lower erosion rate than a plasma sprayed coatings. So, although, relative to a standard 7YSZ coating, the modified coatings have a lower erosion resistance, they still perform better than PS TBCs and their lower thermal conductivities could make them viable alternatives to 7YSZ for use in gas turbine eng
Keywords: EB PVD; TBCs; Erosion; Mechanisms; Microstructure